Long-Term Impact of The Covid Pandemic on the State Budget Through the Review of The Economic Recovery Program in Indonesia - Koko Wahyudi (UNIVERSITAS PGRI YOGYAKARTA, 2022)
Abstract The health, social, economic and monetary sectors have all been affected by the COVID-19 pandemic. To reduce this impact, the government has implemented a plan that prioritizes public safety and security. Developed in times of crisis, the Covid-19 Economic Recovery and Management Plan is very important (extraordinary policy). We must not hand over responsibility, supervision, and good governance in the name of program implementation during the pandemic. The quality of the plan can only be maintained if the objectives and results are not forgotten during implementation. The author conducted a qualitative analysis of relevant primary and secondary data to analyze the PEN policy based on the results of the monitoring and evaluation of the PEN program. The study found that regulations, achievements, data, technical coordination and implementation, monitoring and evaluation, and information technology became challenges for the PEN program. All these barriers are interconnected. Government regulation, statistics, and coordination are all areas where government has made progress. The author argues that the economy can benefit from coordinated efforts between government and community organizations to provide social services, as well as implementing a green economy project model using SWF. Furthermore, the target community method provides another option for gathering more information about people in need of social services. improve ongoing judgment and judgment by making better use of data as it becomes available in real time. Content must be available to businesses, especially SMEs, to advance information technology. At the same time, the quality of financial relationships between federal and local governments, which is a matter of coordination, is currently being revised as part of the regulatory framework. Keywords: Covid-19, review, PEN